Knowledge and attitude of emergency management of avulsed teeth among a sample of Indian parents in Vadodara, Gujarat - Harleen Kaur Soni; Kajol V Jariwala (Wolters Kluwer Medknow Publications, 2020)
Background: Traumatic injuries are commonly seen in children and adolescents, affecting their teeth and supporting structures. The most severe form of traumatic injury is tooth avulsion which leads to major psychological and esthetic problems in children. The prognosis of avulsed teeth significantly depends on prompt and efficient action at the site of the accident, thus requiring that parents or caretakers be knowledgeable about the correct management of this situation. Aim: The objective of the present study was to assess the level of knowledge of parents and caretakers regarding the emergency management for tooth avulsion by the help of a questionnaire. Materials and Methods: The study included 1000 parents of children, aged between 6 years and 12 years, who were asked to fill the modified Ralph and Gregory questionnaire for avulsed teeth. Data were analyzed using SPSS software version 20.00, and descriptive statistics were used to compare the results. Results: Nearly 68.8% of the parents believed in self-replantation, but only 42% would attempt self-replantation themselves. Only 15.4% of the parents felt that replantation should be done immediately. Water and salt solution were the most accepted cleaning medium for avulsed teeth by majority of the parents (77.4%). Almost 92% of the parents were interested in saving the tooth and 2.5% of the parents had encountered previous dental avulsion injuries in children. Conclusion: The study shows a significant lack in knowledge among parents with regard to management of tooth avulsion. There is a definitive need to hold educational campaigns imparting knowledge regarding emergency management of tooth avulsion for parents.